2004
DOI: 10.1021/ja047768u
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Cells Using Composite Nanoclusters of Porphyrins and Fullerenes with Gold Nanoparticles

Abstract: Novel organic solar cells have been prepared using quaternary self-organization of porphyrin (donor) and fullerene (acceptor) units by clusterization with gold nanoparticles on nanostructured SnO2 electrodes. First, porphyrin-alkanethiolate monolayer-protected gold nanoparticles (H2PCnMPC: n is the number of methylene groups in the spacer) are prepared (secondary organization) starting from the primary component (porphyrin-alkanethiol). These porphyrin-modified gold nanoparticles form complexes with fullerene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
403
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(412 citation statements)
references
References 80 publications
5
403
0
1
Order By: Relevance
“…6 Many approaches have been developed to prepare silver and gold nanostructures in different shapes, including nanowires, 7 nanorods, 8 nanospheres, 9-11 nanocubes, 11,12 and nanoplates. 13 Recently, extensive efforts have been devoted to the synthesis of more complex structures -core-shell or hollow nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many approaches have been developed to prepare silver and gold nanostructures in different shapes, including nanowires, 7 nanorods, 8 nanospheres, 9-11 nanocubes, 11,12 and nanoplates. 13 Recently, extensive efforts have been devoted to the synthesis of more complex structures -core-shell or hollow nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Hasobe et al [87,88] reported novel organic solar cells prepared using quaternary self-assembly of porphyrin (donor) and fullerene (acceptor) dye units by clustering with gold or TiO 2 nanoparticles. They demonstrated a remarkable enhancement in the photoelectrochemical performance, as well as broader photoresponse in the visible and infrared relative to the reference systems.…”
Section: Assembly With Materialsmentioning
confidence: 99%
“…In the present work, 5,10,15,20-Tetraphenyl-21,23H-porphin zinc (ZnTPP), CuInS 2 (CIS) and diamond was used for p-type semiconductors [9,16], and C 60 with excellent electron affinity was used for n-type semiconductors. Porphyrin has high optical absorption in the visible spectrum and high hole mobility [17][18][19], and was expected to form cocrystallites with C 60 [20,21] that would be suitable for the bulk heterojunction structure [22,23]. I-III-VI group compounds, called chalcopyrite, are expected as next generation solar cell materials, and CIS is one of the representative chalcopyrite compounds.…”
Section: Open Accessmentioning
confidence: 99%